Territory exclusivity and intergroup encounters in the indris (Mammalia: Primates: Indridae: Indri indri) upon methodological tuning. Issue 1 (1st January 2017) - Bonadonna, G.; Torti, V.; Sorrentino, V.; Randrianarison, R. M.; Zaccagno, M.; Gamba, M.; Tan, C. L.; Giacoma, C.
Abstract: Territorial, socially monogamous species actively defend their home range against conspecifics to maintain exclusive access to resources such as food or mates. Primates use scent marks and loud calls to signal territory occupancy and limit the risk of intergroup encounters, maximizing their energetic balance. Indri indri is a little-studied territorial, socially monogamous singing primate living in family groups. The groups announce territory occupancy with long-distance calls, and actively defend their territories from conspecific intruders. This work includes data collected in three forests in Madagascar on 16 indri groups over up to 5Â years. We aimed (1) to estimate the extent of territories using minimum convex polygon (MCP), implementing minimum sampling effort requirements; (2) to quantify territorial exclusivity, measuring the overlap between territories; and (3) to evaluate the intergroup encounter rate and to quantify the dynamics of group encounters. Our results showed that indris range evenly within exclusive small territories with no or little overlap. Intergroup encounters are rare (0.05 encounters per day), and are located on the periphery of the territories. Disputes were mostly solved with vocal confrontation and only in 13% of the cases ended in physical fights. This frame underlines a costâ€"benefit explanation of territoriality, favouring a strategy that efficiently limits overlap and avoids costly intergroup encounters. We hypothesize that territorial behaviour in indri is related to mate-guarding strategy and that vocal behaviour plays a fundamental role in regulating intergroup spacing dynamics.